Factors contribute to profitability of women entrepreneurs business in textile industry at Kota Bharu / Muhammad Hilmi Ahmad Shafien - Ahmad Shafien, Muhammad Hilmi (2012)
Recognizing the importance of the emerging women entrepreneurs in creating a vibrant and dynamic economy for the nation, the Malaysian Government has been actively promoting women entrepreneurship towards realizing Malaysia’s Vision 2020. However, the research has been undertaken to determine the factors influencing performance and profitability of women entrepreneurs business focusing in textile industry, particularly in Kota Bharu, Kelantan. The objectives of this research are to determine the dominant factor that contributes to profitability of women entrepreneurs business and to determine significant relationship between innovation, motivation, government support and usage of technology associate with the profitability of women entrepreneur business. The study done by using the primary data as sources .The results show that there is some positive relationship between the measurements taken with the profitability of women entrepreneurs business in Kota Bharu. From the result that the researchers have gained, it stated that, innovation, motivation and government support have significant relationship with dependent variable, profitability of women entrepreneurs business. Besides, usage of technology has no significant relationship with the profitability of women entrepreneurs business in Kota Bharu. These results provide significant insights related to women entrepreneurship profitability and their performance levels in Kota Bharu specifically and Malaysia generally.